Epidemiology of Swallowing Disorders in Rheumatoid Arthritis: Prevalence, Risk Factors, and Quality of Life Burden. (September 2018) - Roy, Nelson; Tanner, Kristine M.; Merrill, Ray M.; Wright, Charisse; Pierce, Jenny L.; Miller, Karla L.
Objective: This investigation examined the prevalence, symptoms, risk factors, and quality-of-life burden of swallowing disorders in rheumatoid arthritis (RA), a chronic, progressive autoimmune inflammatory disease. Methods: One hundred individuals with RA (84 women, 16 men; mean age = 61.1 years, SD = 13.1) were interviewed regarding the presence, nature, and impact of swallowing symptoms and disorders. Associations between swallowing disorders, medical factors, RA disease severity, and quality of life were examined. Results: Forty-one percent of participants reported a current swallowing disorder that began gradually and was longstanding (most experiencing symptoms on a daily basis for at least 4 years). Symptoms compatible with solid food dysphagia contributed disproportionately to reporting a current swallowing disorder. Risk factors for dysphagia included a self-reported voice disorder, thyroid problems, esophageal reflux, and being physically inactive. Swallowing disorders increased with self-reported RA disease severity and contributed to a significantly greater burden on overall quality of life. Conclusion: Chronic, longstanding swallowing disorders are common in individuals with RA and appear to increase with disease severity. Those individuals with dysphagia reported greater reductions in quality of life as compared to those without, highlighting the need for improved awareness, exploration, and management of swallowing disorders in this population.